Labor Management Practices of Selected Construction Contractors in Nepal - Doranga, Nabraj; Subedi, Manoj; Katwal, Kamal (International Journal on Engineering Technology, 2024)
The objective of this study is to assess the labor management practices in Class 'A' construction contractors of Nepal. By identifying the challenges and exploring possible remedial measures, the study aims to contribute to the improvement of labor management practices in the industry. The paper is based on primary data and descriptive research design. The findings of the study shed light on several aspects of labor management practices. It was observed that hiring trained and experienced workers was a common practice. However, issues related to poor communication and planning were identified. The study also revealed significant challenges such as inadequate wages, a lack of occupational health and safety measures, an absence of comprehensive labor policies, unfair hearing practices, and insufficient training opportunities. Based on the study's findings, it is recommended that contractors prioritize to employee staffing, performance evaluation, work environment improvement, training initiatives, and compensation management. Addressing these areas can significantly enhance labor management practices.